(untitled) - Dallin, David J. (London, 1949)
A history of Soviet Russia's relations with the Far East and including China, Japan and Korea as well as Central Asia. The period from 1931 to the early 1950's is examined in detail. This volume is the first in a series by the historian David Dallin focused on this area. An important addition to the dearth of histories in English about an important area of the globe.
Keywords: Liên Xô,Soviet Union; Đối ngoại,Foreign relations; Châu Á,Asia